Do government-linked companies underperform? - Feng, Fang; Sun, Qian; Tong, Wilson H.S. (Journal of Banking & Finance, 2004)
Our comprehensive study of 30 Singapore government-linked companies (GLCs) covering the period 1964 to1998 shows that share issue privatization has some positive impacts on their performance. However, there was no evidence that the GLCs were less profitable than a selected group of non-GLCs that match by size and industry. Taking a buy-and-hold strategy, we found that GLC stocks provide statistically equivalent returns relative to market or other control sample returns over various investment horizons of up to four years. Given that GLCs also perform as well as averages for the market and industry up to five years before their listing, we argue that Singapore's government-owned enterprises are comparable to privately run enterprises in efficiency.